Does the timing of integrating new skills affect start‐up growth?. (10th November 2020) - Grillitsch, Markus; Schubert, Torben
Abstract: Research Summary: Growth often requires start‐ups to recruit new skills not present in the founding team. We analyze if the relationship between integrating new skills and growth depends on timing. Should new skills be recruited as early as possible, or can start‐ups add them as needed along the way? Using a unique panel dataset covering Sweden's population of start‐ups from 1997 to 2012, our analysis shows that (a) start‐ups' growth rate is positively correlated with integrating novel skills early in their life, while adding novel skills later is associated with lower growth and (b) corporate spin‐offs profit less from recruiting novel skills than de novo start‐ups. We mirror our results against existing theories and develop theoretical perspectives for future research. Managerial Summary: Entrepreneurs and managers of start‐ups need to develop the competences of their company as it matures. For this, they typically need to hire qualified personnel. But when is the best time to do so? In this paper, we show that the costs of integrating new skills from recruitment increase over time. We show that in order to achieve high firm growth there is a window of opportunity for successful recruitment covering the first 3–4 years after the founding of the company. Recruiting novel skills after this period is associated with reduced firm growth. Our results are thus in favor of a hiring strategy, where needed skills are recruited as early as possible.